Improvement of Hyperphagia by Activation of Cerebral I1-Imidazoline Receptors in Streptozotocin-induced Diabetic Mice - Chung, H. H.; Yang, T. T.; Chen, M. F.; Chou, M. T.; Cheng, J. T. (Hormone and Metabolic Research, 2012)
Imidazoline I1-receptors (I1R) are known to regulate blood pressure and rilmenidine, an agonist, is widely used as antihypertensive agent in clinic. However, the role of I1R in feeding behavior is still unclear. In the present study, we used the agonist of I1R to investigate the effect on hyperphagia in streptozotocin (STZ)-induced diabetic mice. Rilmenidine decreased the food intake of STZ-diabetic mice in a dose-dependent manner. The reduction of food intake was abolished by pretreatment with efaroxan at the dose sufficient to block I1R. Intracerebroventricular (icv) administration of rilmenidine into STZ-diabetic mice also significantly reduced hyperphagia, which was reversed by icv administration of efaroxan. In addition, similar results were observed in STZ-diabetic mice, which received chronic treatment with rilmenidine 3 times daily (t.i.d.) for 7 days. Moreover, the hypothalamic neuropeptide Y (NPY) level was reduced by rilmenidine that was also reversed by pretreatment with efaroxan. In conclusion, the obtained results suggest that rilmenidine can decrease food intake in STZ-diabetic mice through an activation of I1R to lower hypothalamic NPY level.
Keywords: feeding; hyperphagia; imidazoline I1-receptors; neuropeptide Y; STZ-diabetic mice